Laparoscopic liver resection with an 80-degree articulating advanced bipolar device - Ardito, Francesco; Coppola, Alessandro; Longo, Fabio; Giuliante, Felice (Laparoscopic Surgery, 2018)
The video shows the case of a 68-year-old male patient, affected by hemochromatosis, with 3-cm hepatocellular carcinoma in segment 5 on cirrhotic liver. The patient was classified as Child A5, MELD 7, with portal hypertension. An ultrasound-guided laparoscopic resection of segment 5 was planned. Liver resection was carried out by the 80-degree articulating vessel sealer (Aesculap Caiman; B. Braun, Tuttlingen, Germany). The embedded video shows how this device is safe and efficient for laparoscopic liver resection and how its 80-degree articulation jaw may be useful in case of deep or posterior transection planes in order to obtain an adequate oncologic surgical margin.